Psychedelic substitution: altered substance use patterns following psychedelic use in a global survey - Glynos, Nicolas G.; Aday, Jacob S.; Kruger, Daniel; Boehnke, Kevin F.; Lake, Stephanie; Lucas, Philippe (Frontiers in Psychiatry, 2024)
Recent research suggests that psychedelics may have potential for the treatment of various substance use disorders. However, most studies to date have been limited by small sample sizes and neglecting to include non-North American and European populations. We conducted a global, cross-sectional online survey of adults (n = 5,268, 47.2% women) self-reporting past or current psychedelic use and investigated whether psychedelic use was associated with changes in use of other substances. Nearly three-quarters (70.9%; n = 3,737/5,268) reported ceasing or decreasing use of one or more non-psychedelic substances after naturalistic psychedelic use. Among those with previous use, 60.6% (n = 2,634/4,344) decreased alcohol use, 55.7% (n = 1,223/2,197) decreased antidepressant use, and 54.2% (n = 767/1,415) decreased use of cocaine/crack. Over a quarter of the sample indicated that their decrease in substance use persisted for 26 weeks or more following use of a psychedelic. Factors associated with decreased use included a motivation to either decrease one’s substance use or self-treat a medical condition. Importantly, 19.8% of respondents also reported increased or initiated use of one or more other substances after psychedelic use, with illicit opioids (14.7%; n = 86/584) and cannabis (13.3%; n = 540/4,064) having the highest proportions. Factors associated with increased substance use included having a higher income and residing in Canada or the US. Although limited by cross-sectional study design, this large observational study will help inform future studies aiming to investigate the relationship between substance use patterns and psychedelic use.